(untitled) (Annals of Bangladesh Agriculture, 2024)
The Meghna River estuary (MRE) and Tetulia River estuary (TRE) are tropical estuaries on the middle coast of Bangladesh. Hilsa shad (Tenualosa ilisha), is one of the most important anadromous fish (ascending rivers from the sea for breeding), migrates into the Meghna and Tetulia River estuarine systems from the Bay of Bengal. This study assessed the spawning and nursery habitats of hilsa in the Tetulia and Meghna River estuaries by examining the environmental parameters of both estuarine ecosystems. Water samples were collected from nineteen selected sampling sites along and across the estuaries from January to December 2021 covering both the dry and wet seasons. Salinity, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (DIP) concentration varied significantly (p < 0.05) between the MRE and TRE during the dry season. In contrast, no significant variation (p > 0.05) was observed in the salinity, DIN and DIP between the MRE and TRE during the wet season. In addition, no significant variation (p > 0.05) was observed in chlorophyll-a concentration between the MRE and TRE during the dry and wet seasons. The salinity tolerance range is an important driver for the spawning (salinity <0.1 psu) and nursery (salinity <0 2 psu) habitat of hilsa. This study explored that the TRE is suitable for spawning and nursery habitat (salinity <0.09 psu) for hilsa all year round because the TRE acts as a freshwater ecosystem (salinity <0.1 psu) annually. Therefore, the government should focus on protecting and conserving juvenile hilsa (jatka) and brood hilsa in the TRE year round. Ann. Bangladesh Agric. (2023) 27 (1): 57-69